Neural Correlates of Irritability and Potential Moderating Effects of Inhibitory Control - Mariah DeSerisy; Jacob W. Cohen; Huiyu Yang; Bruce Ramphal; Paige Greenwood; Kahini Mehta; Michael P. Milham; Theodore D. Satterthwaite; David Pagliaccio; Amy E. Margolis (Biological Psychiatry Global Open Science)
Background: Irritability affects up to 20% of youth and is a primary reason for referral to pediatric mental health clinics. Irritability is thought to be associated with disruptions in processing of reward, threat, and cognitive control; however, empirical study of these associations at both the behavioral and neural level have yielded equivocal findings that may be driven by small sample sizes and differences in study design. Associations between irritability and brain connectivity between cognitive control and reward- or threat-processing circuits remain understudied. Furthermore, better inhibitory control has been linked to lower irritability and differential neural functioning among irritable youth, suggesting that good inhibitory control may serve as a protective factor. Methods: We hypothesized that higher irritability scores would be associated with less positive (or negative) connectivity between cognitive control and threat-processing circuits and between cognitive control and reward-processing circuits in the Healthy Brain Network dataset (release 10.0; N = 4135). We also hypothesized that these associations would be moderated by inhibitory control such that weaker associations between irritability and connectivity would be detected in youths with better than with worse inhibitory control. Regression models were used to test whether associations between irritability and between-network connectivity were moderated by inhibitory control. Results: Counter to our hypothesis, we detected higher irritability associated with reduced connectivity between threat- and reward-processing and cognitive control networks only in 5- to 9-year-old boys. Inhibitory control did not moderate associations of irritability with between-network connectivity. Conclusions: Exploratory findings indicate that reduced between-network connectivity may underlie difficulty regulating negative emotions, leading to greater irritability.